Promoting advance care planning among community-based older adults: A randomized controlled trial. Issue 11 (November 2016) - Bravo, Gina; Trottier, Lise; Arcand, Marcel; Boire-Lavigne, Anne-Marie; Blanchette, Danièle; Dubois, Marie-France; Guay, Maryse; Lane, Julie; Hottin, Paule; Bellemare, Suzanne
Highlights: An advance care planning intervention was developed for community-based older adults. It involves discussing preferences for future care with a proxy and facilitator. A booklet is offered for recording preferences. Most older adults chose to record their preferences in the booklet. Discussions did not help proxies make more consistent healthcare decisions. Abstract: Objective: To test an intervention designed to motivate older adults in documenting their healthcare preferences in advance, and to guide proxies in making hypothetical decisions that match those of the older adult. Methods: The trial involved 235 older adults, of which half were assisted in communicating their wishes to their proxy. Hypothetical vignettes were used at baseline and twice after the intervention to elicit older adults' preferences and assess their proxy's ability to predict them. Results: By the end of the trial, 80% of older adults allocated to the experimental group had documented their wishes. Changes over time in mean accuracy scores did not differ between groups for any hypothetical situations, except when limiting the sample to dyads that were highly discordant at baseline. Conclusion: The intervention motivated a large proportion of older adults to express their preferences but had little effect on proxies' ability to predict them. Practice implications: Educational tools developed for this study will assist healthcare providers in helping older adults to record their wishes in advance. Clients must be informed of the challenge of making substitute decisions and of the need to discuss the amount of leeway the proxy should have in interpreting expressed wishes.